2012
DOI: 10.7314/apjcp.2012.13.9.4751
|View full text |Cite
|
Sign up to set email alerts
|

Combined EGFR and c-Src Antisense Oligodeoxynucleotides Encapsulated with PAMAM Denderimers Inhibit HT-29 Colon Cancer Cell Proliferation

Abstract: Colon cancer continues to be one of the most common cancers, and the importance and necessity of new therapies needs to be stressed. The most important proto-oncogen factors for colon cancer appear to be epidermal growth factor receptor, EGFR, and c-Src with high expression and activity leading to tumor growth and ultimately to colon cancer progression. Application of c-Src and EGFR antisense agents simultaneously should theoretically therefore have major benefit. In the present study, anti-EGFR and c-Src spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 22 publications
1
12
0
1
Order By: Relevance
“…Our findings are in accordance with a previous study by Nourazarian et al (48), who demonstrated that combined EGFR and c-Src antisense deoxyoligonucleotides inhibited the proliferation of human colon cancer (HT29) cells. It has been reported that the blockade of Src kinase by PP2 attenuates EGFR phosphorylation at both tyrosine-845 and tyrosine-1173 residues in cervical cancer cells.…”
Section: Discussionsupporting
confidence: 94%
“…Our findings are in accordance with a previous study by Nourazarian et al (48), who demonstrated that combined EGFR and c-Src antisense deoxyoligonucleotides inhibited the proliferation of human colon cancer (HT29) cells. It has been reported that the blockade of Src kinase by PP2 attenuates EGFR phosphorylation at both tyrosine-845 and tyrosine-1173 residues in cervical cancer cells.…”
Section: Discussionsupporting
confidence: 94%
“…15 Then, 96-well flat-bottomed culture plates (TPP, Switzerland) were used to seed the cells into them for further MTT assay or 6-well plate (TPP, Switzerland) was applied for real time PCR and flow cytometry. Then they were incubated at 37°C in a 5% CO 2 incubator.…”
Section: Methodsmentioning
confidence: 99%
“…We have established Epidermal growth factor receptor (EGFR) and c-Src antisense oligonucleotide encapsulated with PAMAM dendrimers in human colon cancer cell line and have showed its effects on signalling pathway. 63,68,91 To confirm entry of antisense to the cell, fluorescent microscope and Fluorescence-activated cell sorting (FACS) analysis have been carried out and showed that Fluorescein isothiocyanate (FITS) are conjugated effectively to dendrimers. Our studies evaluated the antisense dendrimers mediated transfer into cells and showed the effective antisense entry inside the cell; however, the antisense alone is not able to enter the cells.…”
Section: Dendrimers-based Antisense Delivery System Approaches For Trmentioning
confidence: 99%